PENGARUH KARAKTERISTIK IBU DAN PELAYANAN ANTENATAL CARE TERHADAP KEJADIAN BAYI BERAT LAHIR RENDAH DI KLINIK PRATAMA BERTA TAHUN 2015 - Juliana Ambarita; Merlina Sinabariba (Elisabeth Health Jurnal, 2016)
Babies born with low birth weight (LBW) are babies born with weight ≤ 2500 grams. The causes of LBW are age, birth spacing, education, antenatal care. Goals : This study aims to analyze the influence of mother characteristics (education, maternal age, age of pregnancy, parity and distance between births) and antenatal care service (ANC) (number of visits and 7T examination components) to events at Primary Maternity Clinic Berta. Methods : This type of research is an observational research using cross sectional design approach. The population is all mothers giving birth at Maternity Clinic Pratama Berta 172 people. The sample amounted to 153 people with simple random sampling technique. Analysis of data with Chi Square and Multiple Logistic Regression (multiple logistic regression). Result : The results showed that the incidence of BBLR of 11.1%. Multiple logistic regression results stated the distance between births (p = 0.027) and the number of visits (p = 0.042) had an effect on the occurrence of LBW. The Exp value (B) of the birth distance is 3.386, so it can be concluded that pregnant women whose birth distance <24 months have 3 times greater probability of baby experiencing LBW and Exp (B) ANC service amounted to 8,496, so it can be concluded that pregnant women His ANC service is not good has a probability 8,496 times larger the baby has LBW. Conclution : For Employees at the Maternity Clinic, Berta provides easy access to ANC services and conducts reproductive health education for pregnant women about the health of pregnant women, the importance of ANC testing during pregnancy and the importance of using long-term contraceptives to regulate birth spacing.